Competition and innovation: An experimental investigation - Donja Darai; Dario Sacco; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2009)
The paper analyzes the effects of more intense competition on firms' incentives to invest in process innovations. We carry out experiments for two-stage games, where R&D investment choices are followed by product market competition. As predicted by theory, an increase in the number of firms from two to four reduces investments. However, a positive effect is observed for a switch from Cournot to Bertrand, even though theory predicts a negative effect in the four-player case. This result reflects overinvestment in the Bertrand case. The results arise both in treatments in which both stages are implemented and in treatments in which only one stage is implemented.
Keywords: C92; L13; O31; 330; R&D investment; intensity of competition; experiment; Forschung; Investition; Wettbewerb; Theorie; Oligopol